Activating Territorial Stigma: Gentrifying Marginality on Edinburgh's Periphery. (June 2014) - Kallin, Hamish; Slater, Tom
This paper reaffirms the importance of politics in theories on gentrification through analysis of a recent 'regeneration' project based in Craigmillar, a stigmatised district on the southeastern edge of Edinburgh. It sketches the historical backdrop to the area's stigma as a place 'outside' the city, using qualitative research on the Craigmillar Festival Society to highlight how this stigma was produced and intensified as well as contested. By stressing that the main intention of the 'regeneration' project was to attract more affluent residents to Craigmillar, we show how territorial stigmatisation and 'regeneration' through gentrification form two sides of the same conceptual and policy coin: the "blemish of place" becomes a target and rationale for 'fixing' the area, thus obviating and obstructing policies aimed at attacking deprivation, inequality, or the structural problems of advanced marginality. The state's role in creating the very stigma it then insists on scrubbing highlights a major contradiction in contemporary urban policy.